Prognostic value of NT-proANP levels on major cardiovascular outcomes in a 31-year follow-up study depends on baseline morbidity - Sakko, Samuli; Perkiömäki, Juha; Ylitalo, Antti; Huikuri, Heikki; Ukkola, Olavi; Koivunen, Peppi; Tapio, Joona (Springer Science and Business Media LLC, 2025)
In subjects with cardiovascular disease (CVD), higher N-terminal proatrial natriuretic peptide (NT-proANP) are associated with major cardiovascular outcomes, while in subjects without CVDs longitudinal data is largely lacking. Our aim was to assess cross-sectional associations between NT-proANP and key CVD factors (1044 subjects, 40-62 years, 51% hypertensive, 49% males) and to evaluate the predictive potential of NT-proANP for HF events, CVD events, CVD mortality, and total mortality over an up-to 31-year follow-up period. In subjects with CVDs, the high NT-proANP tertile had decreased kidney function, higher prevalence of CVDs and adverse echocardiographic measures but also the lowest fasting insulin levels, and in longitudinal analysis had an increased risk for HF events and CVD mortality. In subjects without CVDs the high NT-proANP tertile had the healthiest metabolic profile with the lowest BMI, fasting insulin levels and blood pressure, and in longitudinal analysis weaker evidence for increased risk for HF events and CVD mortality were observed. Regardless of CVDs, NT-proANP levels increased with age and were not independently associated with total mortality. In this middle-aged population, followed for up to three decades, the cross-sectional and longitudinal associations of NT-proANP levels were largely dependent on population characteristics such as age and CVDs.